PERKAWINAN SEMARGA MASYARAKAT BATAK MANDAILING MIGRAN DI YOGYAKARTA - pohan, muslim (Madaniyah, 2018)
SemargaÂ  marriage is a marriage that is prohibited in Batak custom, as one is considered a descendant of blood from the father. There are 3 (three) customary marriage systems, exogamy, endogamy, and eleutrogami. The marriage carried out by the Batak community of Mandailing migrants in Yogyakarta experienced a shift in meaning from the Batak culture, from the exogamy marriage system to the eleutherogami marriage system that did not recognize the prohibition as well as in the exogamy or endogamy marriage system. Factors affecting marital marriage in Batak Mandailing migrants are caused by factors of love, religious factors, economic factors, educational factors and cultural factors. Marriage in the community of Batak Mandailing migrants is done because the Mandailing Batak community migrants have no confidence in the taboo.Perkawinan semarga merupakan perkawinan yang dilarang dalam adat Batak, semarga dianggap satu keturunan darah dari bapak. Ada 3 (tiga) sistem perkawinan adat, exogami, endogami, dan eleutrogami. Perkawinan semarga yang dilaksanakan masyarakat Batak Mandailing migran di Yogyakarta mengalami pergeseran makna dari budaya adat Batak, dari sistem perkawinan exogami menjadi sistem perkawinan eleutherogami yang tidak mengenal adanya larangan sebagaimana halnya dalam sistem perkawinan exogami atau endogami. Faktor-faktor yang mempengaruhi perkawinan semarga dalam masyarakat Batak Mandailing migran disebabkan karena faktor cinta, faktor agama, faktor ekonomi, faktor pendidikan dan faktor budaya. Perkawinan semarga dalam masyarakat Batak Mandailing migran dilakukan karena masyarakat Batak Mandailing migran sudah tidak percaya dengan hal tabu.